Correlation between gut pathogens and fecal calprotectin levels in young children with acute diarrhea - Lam, Yanever Angela; Warouw, Sarah M.; Wahani, Audrey M.I.; Manoppo, Jeanette I.C.; Salendu, Praevilia Margareth (Paediatrica Indonesiana, 2014)
Background In cases of acute diarrhea, it is difficult to distinguish between bact erial and non-bacterial causes . Increased fecal calprotectin (f-CP) level is a marker of neutrophil migration in the intestinal lumen and is associated with intes tinal inflammation. Previous studies reported an increase in f-CP levels in children with acute diarrhea, which is caused by bacteria, but only few have studied the relationship between intestinal pathogens with f-CP levels in acute diarrhea. Objective To assess for a correlation between gut pathogens and fecal calprotectin levels in children with acute diarrhea. Methods We conducted a cross-sectional study between July to November 2012 on children aged 1-5 ye ars with acute diarrhea, and underwent routine blood tests, stool microscopy, f-CP tests, and stool cultures. We used a simple linear regression and correlation analysis with a significance level of P< 0.05. Results Forty-two children enrolled in this study. The mean age of subjects was 2.27 (SD 134) years. Theirmeanf-CP level was 93.88 (SD 14.68) Î¼g/g. On microscopic stool examination, 26 patients ( 61.9%) had positive leukocytes, 1 had Ancy lo stoma duodenale, 1 had Ascaris lumbricoides, and 2 had Blastocystis hominis. Positive stool cultures were found in 14 children (33.3%) with acute diarrhea. There was a significant positive correlation between gut pathogens and f-CP levels (r=0.605; P< 0.0001). Conclusion In young children with acute diarrhea, the average f-CP levels are higher in those with positive intestinal pathogens.